Hak Konstitusional Penyandang Disabilitas dalam Pemilu di Kabupaten Katingan Kalimantan Tengah - Putri, Anasti Caesaristy Permata; Kristanto, Budi (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
The Implementation of inclusive elections is one of the important indicators in the realization of substantive democracy. In Katingan Regency, efforts to fulfill the constitutional rights of person with disabilities in elections have become a serious concern of the local government and election organizers. The study examines in depth the policy implementation,challenges, and improvement efforts in ensuring the political participation of person with disabilities in Katingan Regency. The research uses a qualitative approach with normative-empirical legal research methods. The results show that despite strong legal guarantees, the implementation of the constitutional rightsof person with disabilities in elections still faces various challenges, including physical and information accessibility, a administrative barries, and social stigma. Efforts by the government and the General Election Commission to overcome these challenges include the provision of inclusive voting aids, officer training, and public awareness campaigns. This research recommends strengthening the legal framework, improving accessibility, active participation of people with disabilities, inclusive voter education, and improving the data collection system. In conclusion, commitment and sustained efforts from all stakeholders are needed to realize truly inclusive and accessible elections for people with disabilities, so as to strengthen democracy and realize for equality for all Indonesians. Keywords: Constitutional Rights, Person with Disabilities, Elections